Developing and quantifying indicators of organic farming using analytic hierarchy process. (December 2017) - Sajadian, Masoud; Khoshbakht, Korous; Liaghati, Houman; Veisi, Hadi; Mahdavi Damghani, Abdolmajid
Highlights: A comprehensive set of indices based on organic farming principles by expert sampling. Relative weight of organic farming indicators using AHP. The importance of less considered indicators to achieve organic farming goals. Abstract: Although regulations and criteria relating to organic farming are clearly defined by the relevant agencies, especially by IFOAM, some have been overshadowed by attention to others and have lost their significance over time. The aim of this study was to develop and quantify organic farming indicators to determine the relative importance of each. The desired indicators were collected during a literature review of scientific resources about the principles of organic farming. These indices were classified into four categories and their weights were determined through interviews with experts on organic agriculture, including university professors, agroecology students, Ministry of Agriculture experts, organic farming inspectors and organic farmers. The analytic hierarchy process (AHP) was used for this purpose. The results showed that pest and disease management, yield, soil nutrient management, water consumption rate, chemical fertilizer consumption rate and the use of transgenic materials having weights of 0.16, 0.098, 0.096, 0.08, 0.071 and 0.059, respectively, and are the most important indicators for development and assessment of organic farming. In this as well as similar studies, the weight of indicators associated with consumption of chemical fertilizers and pesticides were relatively high. This indicates the importance of rules related to the use of chemicals in organic farming; however, each index has a certain weight and none can be overlooked. All indicators should be considered as an inseparable set and all should be used in the development of organic farming. The results of this study can be useful for both inspection bodies and organic farmers. Farmers can reduce the risks associated with transitioning to organic farming and minimize the probability of failure by monitoring these indicators in their fields.